A ditadura não vai ao teatro: uma feira brasileira de opinião - Paula, Marcela Oliveira de (2023)
Considering the significant resistance established by the Brazilian theater during the military dictatorship (from 1964 to 1985), an analysis is proposed for five plays gathered in 1978 under the title of Brazilian Opinion Fair, which had their staging prohibited. These plays include Prefácio em forma de peça by Décio de Almeida Prado, O Túnel by Dias Gomes, Janelas Abertas by Gianfrancesco Guarnieri, O Mito by Lauro Cesar Muniz, and Sobrevividos by Leilah Assunção. The book comprises a collection of ten plays with texts authored by representative playwriters of that period – Carlos Henrique Escobar, Carlos Queiroz Teles, Dias Gomes, Gianfrancesco Guarnieri, João das Neves, Jorge Andrade, Lauro César Muniz, Márcio Souza, Leilah Assunção, and Maria Adelaide Amaral – an introduction by Ruth Escobar and a preface written as a play by Décio Almeida Prado. The Brazilian Opinion Fair offers an analysis of the political context of the time and the aesthetic debate within the Brazilian theater. With this perspective and supported by texts discussing the theatrical aspects of the years of the military dictatorship (ARRABAL, 2005; BOAL, 2020; MICHALSKI, 1979; ROSENFELD, 2014), from a historical standpoint (GASPARI, 2014; 2016; SCHWARZ, 1978; REIS, 2014; VENTURA, 2013), and emphasizing the issue of censorship (ALBIN, 2002; FAGUNDES, 1975; GARCIA; SOUZA, 2019; SANTIAGO, 2019), this thesis aims to discuss the tension between ethics and aesthetics in Brazilian playwriting during the Years of Lead, thereby contributing to the politics of memory surrounding that period. For the analysis of the five plays that comprise the publication, texts on theater text theory (PAVIS, 2015; SZONDI, 2011; ÜBERSFELD, 2013), humor (BERGSON, 1980; PROPP, 1992), and studies on the media and the middle class of the time (ALMEIDA; WEIS, 1998; HAMBUGUER, 1998) will also be brought into the discussion.